2009
DOI: 10.1177/1359104509339081
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Clinical Evaluation of the Parents Plus Children’s Programme: A Video-based Programme for Parents of Children Aged 6 to 11 with Behavioural and Developmental Problems

Abstract: This article describes the development and the clinic-based evaluation of the Parents Plus Children's Programme (PPCP), a group-based video-modelling-assisted programme for parents of children aged 6 to 11 referred to a Child Mental Health Service with significant behavioural problems both with and without associated developmental difficulties. In evaluating the programme, a sequential block design was used to assign 74 parents of children referred to the service to the PPCP group (n = 42) or the Treatment as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…The first type, efficacy studies, has studied the effects of PMT when the child has a developmental disability. Such studies include the effect of PMT on parental mental health and/or parenting skills (Tonge et al, 2006;Todd et al, 2010;Davidson, 2011;Gammon & Rose, 1991;Neff, 2012;Niccols & Mohamed, 2000); or child outcomes (Drew et al, 2002); or parent and child outcomes (Chadwick, Momčilović , Rossiter, Stumbles, & Taylor, 2001;Coughlin, Sharry, Fitzpatrick, Guerin, & Drumm, 2009;Feldman & Werner, 2002;Fujiwara, Kato, & Sanders, 2011;Griffin, Guerin, Sharry, & Drumm, 2010;Hand, Raghallaigh, Cuppage, Coyle, & Sharry, 2013;Hudson et al, 2003;McIntyre, 2008aMcIntyre, , 2008bResearch Units on Pediatric Psychopharmacology [RUPP] Autism Network, 2007;Roberts & Pickering, 2010;Quinn, Carr, Carroll, & O'Sullivan, 2006;Tellegen & Sanders, 2014;Whittingham, Sofronoff, Sheffield, & Sanders, 2009). The second type are systematic and literature reviews which also have been conducted on PMT programs for children with a developmental disability (Brookman-Frazee et al, 2006;Gavidia-Payne & Hudson, 2002;Hastings, Robertson, & Yasamy, 2012;Matson et al, 2009;Roberts et al, 2003;Singer, Ethridge, & Aldana, 2007), and review the outcomes of efficacy studies.…”
Section: Previous Reviews and Rationale For Current Studymentioning
confidence: 97%
See 3 more Smart Citations
“…The first type, efficacy studies, has studied the effects of PMT when the child has a developmental disability. Such studies include the effect of PMT on parental mental health and/or parenting skills (Tonge et al, 2006;Todd et al, 2010;Davidson, 2011;Gammon & Rose, 1991;Neff, 2012;Niccols & Mohamed, 2000); or child outcomes (Drew et al, 2002); or parent and child outcomes (Chadwick, Momčilović , Rossiter, Stumbles, & Taylor, 2001;Coughlin, Sharry, Fitzpatrick, Guerin, & Drumm, 2009;Feldman & Werner, 2002;Fujiwara, Kato, & Sanders, 2011;Griffin, Guerin, Sharry, & Drumm, 2010;Hand, Raghallaigh, Cuppage, Coyle, & Sharry, 2013;Hudson et al, 2003;McIntyre, 2008aMcIntyre, , 2008bResearch Units on Pediatric Psychopharmacology [RUPP] Autism Network, 2007;Roberts & Pickering, 2010;Quinn, Carr, Carroll, & O'Sullivan, 2006;Tellegen & Sanders, 2014;Whittingham, Sofronoff, Sheffield, & Sanders, 2009). The second type are systematic and literature reviews which also have been conducted on PMT programs for children with a developmental disability (Brookman-Frazee et al, 2006;Gavidia-Payne & Hudson, 2002;Hastings, Robertson, & Yasamy, 2012;Matson et al, 2009;Roberts et al, 2003;Singer, Ethridge, & Aldana, 2007), and review the outcomes of efficacy studies.…”
Section: Previous Reviews and Rationale For Current Studymentioning
confidence: 97%
“…The sessions also include group discussions and assigned homework (Quinn et al, 2007). Two types of Parents Plus Programmes evaluated in this meta-analysis -Children's Programme (Coughlin et al, 2009;Quinn et al, 2007) for children ages 6-12 years of age, and a modified version of the Children's Programme, adapted to accommodate children with a developmental disability, examined by Hand, Raghallaigh, et al (2013).…”
Section: Types Of Pmtmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown that the Parents Plus Programs are effective in reducing childhood behavior problems and associated parental stress in clinical settings for a variety of age groups (e.g., Behan, Fitzpatrick, Sharry, Carr, & Waldron, 2001;Coughlin, Sharry, Fitzpatrick, Guerin, & Drumm, 2009;Quinn, Carr, Carroll, & O'Sullivan, 2007). In particular, the PPEY Program has been shown to reduce conduct problems, hyperactivity, and parental stress and to help parents move significantly closer to their goals when conducted in a clinical setting by mental health professionals (Griffin, Guerin, Sharry, & Drumm, 2010); however, many parents display limited attendance with clinic-based programs and are less likely to complete treatment (Kazdin, Mazurick, & Bass, 1993), with some parents reporting feeling stigma attached to attending child and adolescent mental health services (Bradby et al, 2007).…”
Section: Parents Plus Programmentioning
confidence: 99%